PENINGKATAN KEMAMPUAN MENGGUNAKAN EJAAN DAN TANDA BACA DALAM MENULIS PENGALAMAN PRIBADI DENGAN TEKNIK JIGSAW SISWA KELAS VII-B SMP NEGERI 1 RENGEL KABUPATEN TUBAN - Kustomo, Heri (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2015)
The research problem is the low ability students at class VII-B SMP Negeri 1 Rengel Tuban in using spelling and punctuation to write personal experience. It is seen from the data: 1) errors capitalization 89.65%, 2) misuse of prepositions 86.20%, 3) misapplication dot 75.86%, and 4) error use commas 41.37% . Researchers chose Jigsaw technique to overcome the problems. This selection was based on the advantages of Jigsaw technique is to learn together, the problems faced by students can be resolved. Results of the study: There was an increase in the ability to use correct spelling and punctuation in writing personal experience of students of class VII-B SMP Negeri 1 Rengel Tuban, namely: 1) errors capitalization decreased by 41.38% from 82.75% to 41, 37%, 2) misuse of prepositions decreased by 13.80% from 79.31% to 65.51%, and 3) the use of punctuation errors decreased by 75.86% from 82.75% to 6.89 %